CERC as a growing research model: analysis of its application in health emergency communication strategies over the last decade - Zurro-Antón, Noelia; Moreno, Ángeles; Humanes, María Luisa (Estudios sobre el Mensaje Periodístico, 2023)
In the wake of recent disease outbreaks, several researchers have pointed out that Crisis and Emergency Risk Communication (CERC) model is useful for guiding strategic communication during health emergencies. It is a priority to see what role this model plays in the international scientific literature. A systematic review of 90 articles published in eight international databases between 2011 and 2021 was conducted. The results confirm that CERC implementation, quantification and systematisation have increased considerably since the start of COVID-19. The statistical and network analysis announces the preponderance of four emerging clusters -intangibles, case studies, message content analysis and the role of social media-. The study identifies some challenges for public relations research and practice during future health emergencies like skin cancer.